2018
DOI: 10.1021/acsomega.8b00537
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Biomacromolecule Absorption and Long-Term Release by Graphene Oxide

Abstract: Biomacromolecule loading is the popular research in the biomedical field. To control the loading amount and releasing profile, various materials and fabrication techniques were developed. In this study, layer-by-layer assembly of multilayer films between collagen (Col) and graphene oxide (GO) was used to control the release of the loading molecule. By mixing GO into the system, ovalbumin (OVA) can be spontaneously adsorbed onto the GO sheet (denoted as GO/OVA) via the hydrophobic interaction. Two kinds of mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…In our studies, a direct redox reaction between GO and the substrates was excluded by running independent samples without CYP enzymes. It has been reported previously that GO has an exceptionally high capability of spontaneously binding to proteins 33 and other macromolecules, 34 and it depends on the number of oxide-containing groups on the surface. 35 Thus, it is probable that GO bound the substrate or prevented the substrate from entering the active site of CYP by binding to microsomes.…”
Section: Discussionmentioning
confidence: 99%
“…In our studies, a direct redox reaction between GO and the substrates was excluded by running independent samples without CYP enzymes. It has been reported previously that GO has an exceptionally high capability of spontaneously binding to proteins 33 and other macromolecules, 34 and it depends on the number of oxide-containing groups on the surface. 35 Thus, it is probable that GO bound the substrate or prevented the substrate from entering the active site of CYP by binding to microsomes.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to coat macroscopic surfaces presents GO Sheet as a potentially useful coating for biomedical devices, Spontaneous protein adsorption on Graphene Oxide nanosheets allowing efficient intracellular vaccine protein delivery [27]. HDLC materials have been shown to exhibit biocompatible surface properties [8] [9] [10]. It can be anticipated that GO sheet will also be biocompatible [9] [28] and may offer improved properties by harvesting [29] related to the highly ordered structure.…”
Section: Resultsmentioning
confidence: 99%
“…Graphene is comprised of a lattice of carbon atoms in a hexagonal array, creating an ordered structure against which morphology of immobilized biomolecules can be easily discerned. We have demonstrated here that the GO can be prepared from A-HDLC as large solid-state sheets to produce an ordered structure which can be used as a solid support substrate on which biomolecules can be immobilized, spontaneously adsorbed [10].…”
Section: Introductionmentioning
confidence: 99%
“…LbL films can incorporate functional polymers [ 24 ], enzymes [ 25 ], small molecules [ 26 ], polysaccharides [ 27 ], carbon nanotubes (CNT) [ 28 ], nucleic acids [ 29 , 30 ], or inorganic nanoparticles (NPs) [ 31 ] and can be assembled in a wide range of substrates independently of their size or shape, allowing for the creation of three-dimensional objects covered in these films [ 3 , 32 ]. The fact that LbL films can be deposited on different substrates without altering the properties of the films is very useful, because it allows the testing of different film characteristics, which may require different substrates [ 9 , 33 ], for example, the quartz crystal microbalance (QCM), which requires the films to be assembled in a QCM crystal sensor/lamella [ 34 , 35 ], or the transmission electron microscopy, for which the films need to be deposited onto copper grids [ 36 , 37 ]. This also allows for their application in multiple biomedical devices without fear that their properties will change.…”
Section: Graphene Oxide Multilayer Filmsmentioning
confidence: 99%
“…There are several studies using ovalbumin (OVA—the main protein found in egg white, largely used as a nutrient supplement) as model drug; some authors were able to use GO either as a nanocarrier or a capping layer to build thin films, preventing the early release of the biomacromolecule and obtaining, therefore, a long-term delivery that lasted over 70 days [ 35 ]. This mechanism was also applied in films containing OVA as the model protein/drug and PBAE as a hydrolytically degradable polymer.…”
Section: Graphene Oxide For Controlled Drug Releasementioning
confidence: 99%